2011
DOI: 10.1159/000326910
|View full text |Cite
|
Sign up to set email alerts
|

Functional Disability Profiles in Amnestic Mild Cognitive Impairment

Abstract: Background/Aims: Instrumental activities of daily living (IADL) can be impaired in mild cognitive impairment (MCI), and the severity of functional disability predicts Alzheimer’s disease (AD) in amnestic MCI (aMCI). This study investigated the functional profiles of aMCI in a Chinese population. Methods: The Disability Assessment for Dementia scores of 56 subjects with single-domain aMCI (sd-aMCI) and 94 with multiple-domain aMCI (md-aMCI) were compared with normal controls (n = 64) and mild AD patients (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 68 publications
(51 reference statements)
8
53
0
3
Order By: Relevance
“…We, as well as others, assumed that a mild decline in cognitive capacities is accompanied by a certain decline in complex functioning [9][10][11]. In this study we found that a-ADL decline, measured by the a-ADL-DI and a-ADL-CDI correlated with cognitive decline as measured by MMSE and CamCog.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We, as well as others, assumed that a mild decline in cognitive capacities is accompanied by a certain decline in complex functioning [9][10][11]. In this study we found that a-ADL decline, measured by the a-ADL-DI and a-ADL-CDI correlated with cognitive decline as measured by MMSE and CamCog.…”
Section: Discussionsupporting
confidence: 67%
“…Advanced ADL (a-ADL) are more sophisticated activities, beyond those necessary to live independently. When trying to establish the diagnosis of Alzheimer's disease (AD) in an early stage, assessment of a-ADL can be of great interest since these activities demand high cognitive functioning and are, therefore, more responsive to subtle changes [9][10][11]. However, at this moment it is still uncertain which domains of functioning may be impaired and to what extent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the unsystematic use and variability of the functional assessments employed have impaired more accurate results. [46][47][48][49] We know that there are many scales for the assessment of ADL in the elderly. However, they were created with the objective of assessing the functional decline in elderly people with dementia, whose deficit proves to be more significant when compared to elderly people with MCI.…”
Section: Criterion Validitymentioning
confidence: 99%
“…The literature shows that elderly that maintain normal cognitive performance are younger 3 , have higher levels of schooling and income 1,4 , display higher levels of community participation 5 , and perform activities that involve physical, mental, and social stimulation 6 . In addition, alterations in functional capacity can precede cognitive impairment 7,8 .…”
Section: Introductionmentioning
confidence: 99%